Energy-efficient MAC protocols for wireless sensor networks: a survey - Abdelmalek Djimli; Salah Merniz; Saad Harous (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
MAC Protocols enables sensor nodes of the same WSN to access a common shared communication channel. Many researchers have proposed different solutions explaining how to design and implement these protocols. The main goal of most MACs protocols is how to prolong lifetime of the WSN as long as possible by reducing energy consumption since it is often impossible to change or to recharge sensors’ batteries. The majority of these protocols designed for WSN are based on “duty-cycle” technique. Every node of the WSN operates on two periods: active period and sleep period to save energy. Until now (to our knowledge) there is no ideal protocol for this purpose. The main reason relies on the lack of standardization at lower layers (physical layer) and (physical) sensor hardware.  Therefore, the MAC protocol choice remains application-dependent. A useful MAC protocol should be able to adapt to network changes (topology, nodes density and network size). This paper surveys MAC protocols for WSNs and discusses the main characteristics, advantages and disadvantages of currently popular protocols.